Regulatory and Legal Provision of the Public Administration of the Development of the Road Industry of Ukraine - Tymokha, Anatolii (Pressing Problems of Public Administration, 2024)
The paper examines the transformation of regulatory and legal provision of public management of road development in Ukraine under the influence of military aggression and the need for post-war reconstruction. The inconsistency of the current legal framework with the challenges of wartime was revealed, in particular, in the field of coordination of actions of different levels of government, financial support, prioritization of infrastructure restoration and public involvement. Gaps and conflicts in the legal framework were identified, which prevent effective public management and reconstruction of the road network. The experience of Georgia and Israel in overcoming similar challenges is analyzed, in particular, by adapting legislation, creating specialized management bodies, implementing electronic management systems and attracting international assistance. On the basis of the obtained results, scientifically based recommendations were developed for the improvement of regulatory and legal support and mechanisms of public management of the development of the road industry of Ukraine, aimed at increasing their efficiency, transparency and adaptability to modern challenges.